The gospel of the son of God an introduction to Matthew - Bauer, David R. (Westmont InterVarsity Press, 2019)
From beginning to end, the Gospel of Matthew emphasizes that Jesus is the Son of God. In this comprehensive introduction to Matthew, David Bauer presents a holistic inductive approach with a literary, theological, and canonical focus. Exploring issues of genre, interpretive methods, authorship, audience, and literary structure, he also guides readers through interpretation and emerging theological themes.
Cover -- Title Page -- Copyright -- Dedication Page -- Contents -- Preface -- Acknowledgments -- Abbreviations -- Introduction -- Part 1: Orientation -- 1 Form and Genre -- 2 Approach and Method -- 3 Circumstances of Composition -- 4 Shape of Composition -- Part 2: Interpretation -- 5 Interpretation of Matthew 1:1-4:16 -- 6 Interpretation of Matthew 4:17-16:20 -- 7 Interpretation of Matthew 16:21-28:20 -- Part 3: Reflection -- 8 Jesus: The Christological Titles -- 9 Jesus: Additional Aspects of Christology -- 10 God -- 11 Salvation History and Eschatology -- 12 Discipleship -- Bibliography -- Author Index -- Scripture Index -- Praise for The Gospel of the Son of God -- About the Author -- More Titles from InterVarsity Press.
Description based on publisher supplied metadata and other sources
Keywords: Electronic books